PROSECUTING RAPE ATROCITIES IN TIGRAY: SHOULD INTERNATIONAL CRIMINAL COURT TAKE OVER THE CASE? - Made Ananda Bella Cahyani; I Made Budi Arsika (Diponegoro Law Review, 2023)
Thousands of women in Tigray have experienced massive atrocities of rape since early November 2020, the beginning of the wage of war between the Tigray People’s Liberation Front and the Ethiopian Government. This article examines rape in Tigray as a war crime and analyzes the prospect of holding perpetrators criminally responsible before the International Criminal Court (ICC). This paper is legal research using the statutory, case, fact, and conceptual approaches. The result suggested that there exist war crimes of rape in Tigray. In order to achieve justice for the victims and the sake of a sense of the humanity of people over the world, the case must be tried before an impartial and reliable court, which in this regard, is the ICC. Facts that both Ethiopia and Eritrea are not state parties of the Rome Statute of the ICC do not prevent the case from being prosecuted before the ICC. The most potential means is that international society urges the United Nations Security Council to refer the present case before the ICC to hold the perpetrators criminally responsible.